Strategic Planning and Asset Management in Increasing Generation Z Investment Interest in Paya Bengkuang Village - Kayla Aulia Rahma; M Chaerul Rizky; Dewi Nurmasari Pane; Emelia Santika Br Sembiring; Hikmal Fuady (Jurnal Manajemen, Informatika, Rekayasa Perangkat Lunak dan Teknologi Komunikasi, 2026)
This study aims to analyze the influence of strategic planning and asset management on Generation Z's investment interest in Paya Bengkuang Village. The research employed a quantitative approach using a survey method by distributing questionnaires to 60 respondents selected through saturated sampling techniques. Data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis with the assistance of SPSS software. The results indicate that strategic planning has a positive and significant effect on investment interest, with a t-value of 3.167 and a significance level of 0.002 (<0.05). Asset management also has a positive and significant effect on investment interest, with a t-value of 2.328 and a significance level of 0.024 (<0.05). Simultaneously, strategic planning and asset management significantly influence investment interest, as evidenced by an F-value of 7.676 and a significance level of 0.001 (<0.05). The coefficient of determination (R²) of 0.212 indicates that 21.2% of the variation in investment interest can be explained by strategic planning and asset management, while the remaining 78.8% is influenced by other factors outside the research model. The findings also reveal that strategic planning has a more dominant influence than asset management in increasing Generation Z's investment interest in Paya Bengkuang Village. Therefore, improving strategic planning and asset management capabilities is essential to enhance investment interest among young people.